AKIBAT HUKUM TERHADAP OBJEK JAMINAN FIDUSIA ATAS KETERLAMBATAN PENDAFTARAN PADA KANTORPENDAFTARAN FIDUSIA - HARI JULIO (PREMISE LAW JURNAL, 2017)
Manual registration of fiduciary collateral at the Fiduciary Collateral Office through the process of administering and issuing fiduciary collateral certificate takes a long time and spends a lot of money. By the online system used in the administration of fiduciary collateral registration, registering it becomes easy. The online system was based on the Decree of the Minister of Law and human Rights No. 9/2013 on the Imposition of the Electronic Fiduciary Collateral Registration and the Presidential Decree No. 21/2015 on the Procedure of Electronic Fiduciary Collateral Registration in order to increase services to people who need legal service in fiduciary collateral. The research problems are as follows: how about the procedure of registering fiduciary collateral by online, how about the role of a Notary in registering the fiduciary collateral, and how about the settlement of the lateness in registering the fiduciary collateral by online. The research used juridical normative and descriptive analytic method by using primary, secondary, and tertiary legal materials. The data were gathered by conducting interviews and library research while the conclusion is drawn deductively. Keywords: Legal Consequence, Registration by Online, Fiduciary Collateral